Hubungan Pemanfaatan Platform Zep Quiz Dengan Minat Belajar Peserta Didik Dalam Pembelajaran Ppkn Di Kelas VIII SMP Negeri 1 Garut - Ardani, Nopita; Maulana, Ana (Universitas Muhammadiyah Ponorogo, 2026)
This study aims to analyze the relationship between the use of the Zep Quiz platform and students' learning interest in Pancasila and Citizenship Education (PPKn) in eighth grade students of SMP Negeri 1 Garut. This study is based on the phenomenon of low student learning interest in subjects that tend to be normative and conceptual. The method used is a quantitative approach with an ex post facto correlational design. The population and sample of the study included 48 eighth grade students selected through a saturated sampling technique. Data were collected using a closed-ended questionnaire based on a Likert scale that had previously been tested for validity and reliability to measure the variables of Zep Quiz utilization and student learning interest. Data analysis was carried out using Pearson correlation tests and simple linear regression, after ensuring that all prerequisites for statistical analysis, including residual normality, had been met. The results of the study indicate a very strong and significant positive relationship between the use of the Zep Quiz platform and student learning interest. This finding indicates that the more optimal the use of Zep Quiz in PPKn learning, the higher the student's learning interest. Thus, the integration of gamification-based learning media has been shown to have strategic potential in increasing student engagement and motivation in junior high school. This research provides empirical evidence for the development of gamification-based PPKn learning and can serve as a reference for educators and policymakers in designing interactive, contextual, and student-centered digital learning.